How do Polish learners of English rate bilingual and monolingual dictionaries? - Lew, Robert (Université De Bretagne Sud, 2004)
The topic of this paper is the evaluation by Polish learners of English of bilingual and monolingual dictionaries used by those learners. Data for the paper come from 712 Polish learners of English representing a broad range of EFL proficiency levels. Subjects were asked to rate two dictionaries: their dictionary of first choice and their dictionary of second choice. The effect of choice as a predictor variable is also explored. A tendency is revealed for the mid-level competence learners to give the lowest ratings to their dictionaries. Monolingual dictionaries were given significantly higher ratings than bilingual dictionaries. Subjects rated dictionaries of first choice more highly than their second-choice dictionaries.
Keywords: Lexicography; Dictionaries; Dictionary preference; EFL